Utilization of Catechins in Sunscreen Lotion Formulation - Sefrianita Kamal; Mesa Sukmadani Rusdi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
Skin is the outermost part of the body which is susceptible to solar radiation. Excessive radiation from ultraviolet (UV) rays can harm the skin, such as premature aging effect, erythema, and even skin cancer. Antioxidant compounds are needed to protect the skin from excessive exposure of UV rays. The antioxidant can be useful as a defense system against free radicals, ultraviolet radiation, and air pollution. One source of antioxidant from nature is Catechins. Catechins are obtained from the isolation of gambir (Uncaria gambir Roxb). Besides being useful as an antioxidant, Catechins also has antibacterial, antiseptic and wound healing effect. The antioxidant activity of Catechins can absorb UV rays, provides protection against oxidative stress, inflammation, and skin cancer. Therefore, the research is necessary to utilize the catechins in sunscreen lotion formulation. Catechins are isolated from gambir by maceration with hexane and ethyl acetate (polar, nonpolar and residual fractions). The fraction which yields the most catechins is used as the active substance in the formulation. The formulation is divided into 4 lotion formulas, namely Formula 1 with 0.5% catechins concentration, Formula 2 with 7.5% catechins concentration, Formula 3 with 1% catechins concentration, and Formula 4 without catechins substance. Physical stability test and effectiveness of sunscreen formulation are carried out on 4 lotion formulas. Physical stability tests included organoleptic observation, homogeneity, pH, and assessment of the effectiveness of sunscreen formulation by using UV-Vis Spectrophotometer.